2007
DOI: 10.1007/s11434-007-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Trace elemental records of short-lived heating during exhumation of the CCSD eclogites

Abstract: Trace element compositions of garnet, omphacite and apatite in ultrahigh-pressure eclogites from the main hole of the Chinese Continental Scientific Drilling (CCSD) project were in situ analyzed by the LA-ICP-MS method. Although both garnet and omphacite have homogeneous major element compositions, their trace elements show zonations from core to rim in rare earth elements. In particular, middle rare earth elements in the garnet, heavy rare earth elements in the apatite and all rare earth elements in the ompha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…Although fully crystallized, the polyphase Ab-or Kf-bearing inclusions in the Sulu eclogites are compositionally similar to silicate glass inclusions in the Pamir eclogite xenoliths, and so might also represent mica partial melting at HP or UHP conditions. Updated studies on the Sulu-Dabie UHP rocks demonstrated that the subduction and exhumation of this slab is characterized by dry subduction [8,9] and hot exhumation [4,[31][32][33][34] . Results from studies of petrography, stable isotopes, and fluid inclusions all suggested only restricted amounts of aqueous fluid were available to both prograde and retrograde metamorphic reactions in the Dabie-Sulu UHP eclogites [8,9,66] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although fully crystallized, the polyphase Ab-or Kf-bearing inclusions in the Sulu eclogites are compositionally similar to silicate glass inclusions in the Pamir eclogite xenoliths, and so might also represent mica partial melting at HP or UHP conditions. Updated studies on the Sulu-Dabie UHP rocks demonstrated that the subduction and exhumation of this slab is characterized by dry subduction [8,9] and hot exhumation [4,[31][32][33][34] . Results from studies of petrography, stable isotopes, and fluid inclusions all suggested only restricted amounts of aqueous fluid were available to both prograde and retrograde metamorphic reactions in the Dabie-Sulu UHP eclogites [8,9,66] .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that decompression from eclogite to granulite facies was nearly isothermal [50][51][52] , suggesting a rapid exhumation from ~230 Ma to ~215 Ma. However, updated studies suggested that the Sulu UHP rocks experienced a "hot" exhumation [4,34] characterized by a short pulse of heating and increase of temperature [31][32][33] .…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an increase in temperature at decreasing pressure would occur at the initial exhumation of the deeply subducted continental crust. An in-situ study of trace elements in minerals from CCSD-MH eclogite also suggests short-lived heating during the exhumation (Zong et al, 2007). Therefore, the ''hot'' exhumation is evident for the UHP metamorphic rocks in the Sulu orogen.…”
Section: Partial Melting During Exhumationmentioning
confidence: 93%
“…Almost all of these studies have focused on UHP metamorphic processes, while only a few studies have focused on the thermal evolution of the Dabie-Sulu UHP terrane. Trace elemental zoning of garnet, apatite and omphacite as well as Ti-in-zircon geothermometers of some eclogites from the main hole of the Chinese Continental Scientific Drilling Project (CCSD-MH) recorded a shortlived heating event during exhumation of the terrane Zong et al, 2007). This is consistent with the overprinting of granulite-facies metamorphism on some eclogites in the Sulu UHP terrane (Banno et al, 2000;Nakamura and Hirajima, 2000;Wang et al, 1993;Yao et al, 2000), which has generally been attributed to high temperatures that prevailed during exhumation over a very short time scale (e.g., the Moldanubian Zone) (O'Brien, 1997;O'Brien and Vrána, 1995).…”
Section: Introductionmentioning
confidence: 99%